Evaluation of the runway capacity of the Ninoy Aquino International Airport - Sawali, Francis Carlo A.; Vega, Larisa Viktoria U.
The Ninoy Aquino International Airport (NAlA) is currently experiencing congestion because the demand for operations is greater than the airport's capacity. To solve this problem, this study aims to increase the runway capacity of NAIA. This study was conducted to adjust the current sequence of flights so that more operations may be accommodated per day. With a higher runway throughput, structural projects and expansions will not be necessary to serve current and projected additional flights. Runway use must be systematical in order to lessen delays due to operational procedures that are experienced by travelers. Airport operation rules and analysis on actual observations were applied in order to optimize runway utilization. Algorithms were created in order to generate an adjusted schedule of flights with a higher capacity of 47 aircraft movements per hour, or 7 operations more than the current declared value. The same principle was applied to observed flights; hence the maximum capacity of the runway is now 52 aircraft movements per hour, or 8 operations more than the current maximum capacity.